Measurement of the passive fast-ion D-alpha emission on the NSTX-U tokamak. (8th January 2018) - Hao, G Z; Heidbrink, W W; Liu, D; Podesta, M; Stagner, L; Bell, R E; Bortolon, A; Scotti, F
Abstract: On National Spherical Torus Experiment Upgrade, the passive fast-ion D-alpha (passive-FIDA) spectra from charge exchange (CX) between the beam ions and the background neutrals are measured and simulated. The results indicate that the passive-FIDA signal is measurable and comparable to the active-FIDA on several channels, such as at the major radius R  = 117 cm. Here, active-FIDA means the active D-alpha emission from the fast ions that CX with the injected neutrals. The shapes of measured spectra are in agreement with FIDASIM simulations on many fibers. Furthermore, the passive-FIDA spatial profile agrees with the simulation. When making measurements of active-FIDA in the edge region using time-slice subtraction, variations in the passive-FIDA contribution to the signal should be considered.